ИЗ ЗАЛА СОВЕТА: ОПЫТ ЧЛЕНОВ СОВЕТА ПО РАЗВИТИЮ ПРАКТИКИ ВЗАИМОДЕЙСТВИЯ С ОБЩЕСТВОМ В МЕСТНОМ САМОУПРАВЛЕНИИ - А.Синау; Х.Саид; В.Хасан (Вопросы государственного и муниципального управления, 2025)
The Republic of Maldives is a small island nation with more than 1120 small islands, divided into 20 groups of islands known as Atolls. The atolls are decentralised and governed by an elected council. The current study explores the community engagement practices of councillors in the Maldives. Using a qualitative approach, semi-structured interviews were conducted with twenty councillors. The councillors were selected from city, atoll and island councils, using a purposive sampling technique, to explore their current community engagement practices, identify challenges and gather recommendations for improvement. The findings reveal that most councillors engage in traditional methods, such as public meetings, community workshops and social media. Nevertheless, challenges such as low public participation, differences in political views, resource constraints and internal leadership issues hinder effective engagement with the community members. Hence, councillors recommend diversifying engagement strategies, implementing leadership training, allocating more resources, fostering trust and tailoring community engagement practices suitable for the specific community. Thus, the study emphasises the need for innovative and inclusive community engagement practices to improve governance and collaboration between the councillors and the community. Future studies can adopt a quantitative approach to find out the factors that affect community participation from the perspective of the community members.